International Dividend Repatriations - Lehmann, Alexander; Mody, Ashoka (Washington, D.C. : International Monetary Fund, 2004)
Income earned by the branches and subsidiaries of multinational firms can be either reinvested in the host country or repatriated as dividends to the firms' headquarters. Despite the rapid growth of foreign direct investment in the 1990s, there has been relatively limited analysis of the dividend behavior of multinationals. We find that investors in multinationals from the two largest foreign- investing countries-the United Kingdom and the United States-require a steady flow of dividends, consistent with a view that such regular dividend payments are a mechanism through which to discipline host-country managers. In contrast, German investors, who tend to invest in riskier countries, do not appear to demand persistent dividend payments. Changes in income also influence dividends. This payout ratio from income appears, for example, to be lower for less risky countries. Finally, the evidence suggests that dividend payments do not necessarily aggravate the balance of payments position during crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States